DEVOSI KEPADA BUNDA MARIA MELALUI DOA ROSARIO DEVOSI KEPADA BUNDA MARIA MELALUI DOA ROSARIO DEVOSI KEPADA BUNDA MARIA MELALUI DOA ROSARIO DEVOSI KEPADA BUNDA MARIA MELALUI DOA ROSARIO DEVOSI KEPADA BUNDA MARIA MELALUI DOA ROSARIO DEVOSI KEPADA BUNDA MARIA - Lumbanbatu, Johannes Sohirimon; Sihaloho, Lusiana (IN VERITATE LUX, 2020)
Devotion to the Virgin Mary is a sincere and deep-seated act of reverence accompanied by a surrendering attitude towards her. It is an integral part of the Church's faith teachings. Through devotion to the Virgin Mary, believers honor her as the Mother of God, especially considering her role in God's plan for the world through Jesus. One form of devotion to the Virgin Mary is the Rosary, which serves as a means of deepening faith, particularly among mothers. Through communal prayer with the Virgin Mary, mothers strive to emulate her unwavering hope and perfect love, thus becoming models for all believers to follow. In this context, members of the Catholic Women's Association at St. Clare of Assisi Parish in Sirungkungon seek to imitate Mary's faith. Mary serves as a powerful example for mothers, guiding them in deepening their relationship with God. The research findings indicate that engaging in devotion to the Virgin Mary through the Rosary significantly impacts believers' spiritual growth and daily lives, fostering positive outcomes in personal, community, and Church settings